Um olhar sobre os rankings universitários: o impacto e a repercussão - Silva, Antonio Carlos Lopes da (Universidade Federal de São Carlos, 2021)
Studies in the field of Science, Technology and Society (STS) highlight the urgency of society's participation in the development of science, technology and innovation. Federal Institutions of Higher Education (IFES), as social organizations, in turn, fulfill their role of disseminating the knowledge developed and produced within their walls by various means, among which we can highlight the partnerships made with other institutions in the public sphere, how much of the private. It is in this context that involves the CTS field and the IFES, that we will look at this new (not so new) way of evaluating university institutions: university rankings. Historically in Brazil, the wave of university rankings began in the 1980s, at the initiative of Editora Abril, when the Playboy Magazine launched, in 1981, the first version of the Melhores Faculdades ranking. As of 2012, the company Folha de São Paulo (FSP) launched the Folha University Ranking (RUF), the main ranking of Brazilian universities. Worldwide, the pioneering of the USA stands out, where the first publications evaluating higher education emerged around 1910. The evolution of rankings culminated in the creation of the great rankings of world-class universities. Regarding university rankings, two findings are evident: first, they are here to stay; second, the disclosure of ratings provokes different reactions from interested actors. If, on the one hand, critics point to methodological frankness, marketing interests or the impartiality of the indicators, among other factors, on the other hand, there is the exaltation of institutions that appear well classified, which confirms the growth of interest in university rankings in the last decade. Given these facts, the research proposed here will seek to identify how the managers of federal educational institutions (IFES) are manifesting here in the sense of those who promote the development of teaching, research and extension, in view of the publication of university rankings. In this context, the present work has as general objective to identify how the manifestations of the federal institutions of higher education, represented by their managers, are in front of the growing presence of university rankings in the media, specifically, in the moments of the results release. The question to be answered: is it possible to identify the intentions of the IFES managers through their statements and declarations with the publication of the results of university rankings on websites? The research focused on the search for manifestations on university rankings entirely through virtual means, using the Google search engine and the IFES' own search engines. In the research, 757 manifestations on the Internet about university rankings were collected and analyzed, of which 462 contained information about the institutions object of this research. Of this subtotal, 147 contained statements by representatives of the IFES, in the figures of rectors, pro-rectors, course coordinators, directors, among others, on which the qualitative analyzes were carried out. This practice used in the research was not able to identify the intention of most of the IFES to use planned actions that would make it possible to obtain improved performance in rankings.
A look at university rankings: impact and repercussion
Keywords: Rankings universitários; Avaliação do ensino superior; Universidades de classe mundial; University rankings; Evaluation of higher education; World-class universities; CIENCIAS HUMANAS